2016
DOI: 10.1007/s12035-016-9792-7
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of the Good and Bad: Remodeling of the Microtubule Network in the Brain by Cdk5

Abstract: Cdk5, a cyclin dependent kinase family member, is a global orchestrator of neuronal cytoskeletal dynamics. During embryogenesis, Cdk5 is indispensable for brain development. In adults, it is essential for numerous neuronal processes, including higher cognitive functions such as learning and memory formation, drug addiction, pain signaling and long term behavior changes through long term potentiation and long term depression, all of which rely on rapid alterations in the cytoskeleton. Cdk5 activity becomes dere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 118 publications
(111 reference statements)
1
34
0
Order By: Relevance
“…Cdk5 is a member of the cyclindependent kinase family, which has been implicated in drug addiction, pain signaling, microtubule dynamics, and learning and memory formation (95,96). Cdk5 is abundant in neuronal cells and is activated by complexing with p35 or p39 protein.…”
Section: Potential Mediators Of Xbp1 Signaling In Neuronsmentioning
confidence: 99%
“…Cdk5 is a member of the cyclindependent kinase family, which has been implicated in drug addiction, pain signaling, microtubule dynamics, and learning and memory formation (95,96). Cdk5 is abundant in neuronal cells and is activated by complexing with p35 or p39 protein.…”
Section: Potential Mediators Of Xbp1 Signaling In Neuronsmentioning
confidence: 99%
“…It is well known that cdk 5 dysregulation may cause neuroinflammation and neurodegeneration [51] One study demonstrated that in response to Aβ, neurons will reenter the cell cycle and transit through the cell cycle until the M phase, and that these processes are mediated by CDK 5 and its downstream effectors. So, the importance of CDK 5 as a neuronal ''switch'' is due to the fact that aberrant hyperactivation of CDK 5 by the production of truncated activator p25 results in the formation of hyperphosphorylated TAU, neuroinflamation, amyloid deposition and neuronal death in vivo and in vitro [52].…”
Section: +mentioning
confidence: 99%
“…Cyclin-dependent kinase-5 (Cdk5) shares high homology with other family members; however, it differs from them by adopting unique activation strategies and distinctive cellular functions [35]. Cdk5 is not activated by classical cyclins such as cyclin A, cyclin D, and cyclin E but binds to its own specific protein partners, p35, p39, and cyclin I [68].…”
Section: Introductionmentioning
confidence: 99%